Model Telediagnosis Serangan Jantung untuk Para Praktisi Kesehatan Menggunakan Mobile Phone - Legowo, Nilo; Suryaputra, Renan Prasta J. Devin; Winarya, Candy (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The lack of medical experts such as doctors at rural areas resulted in some problems such as the high cost of medical care and low service of doctors and medical resource provider. The conditions results in an idea to implement a communication system between rural medical practitioners and doctors in urban areas to perform remote diagnosis on patients (telediagnosis). The research involves several parties such as doctors, health centers, health practitioners (paramedics), patients, and hospitals and health institutions. The telediagnosis system development consists of the construction of a software application prototype as media input for patient data which will be sent to doctors at town, database systems design, integration of basic multimedia devices, medical diagnostic device integration, and application testing of telediagnosis performance using an android-based mobile application. Data integration patterns include patient data delivery patterns, checking a patient's diagnosis, saving and continuing to the physician or health care practitioner with real-timesystem. This study is conducted according to standard research stages: problem collection, problem analysis, research materials collection, research design, and research implementation. Telediagnosis system is used to facilitate remote diagnosis of patients at rural areas which is able to serve patients more quickly, and helps find out nearest location for patients to get medicines as well as recommendation of nearest hospital. This system helps decrease the workload of hospitals.